Sudden Decompensation of Patients Admitted to Non-ICU Settings Within 24 h of Emergency Department Admission. (April 2023) - Taveras, Anabelle N.; Clayton, Lisa M.; Solano, Joshua J.; Hughes, Patrick G.; Shih, Richard D.; Alter, Scott M.
Background: Patients admitted to the hospital floor (non-intensive care (ICU) settings) from the emergency department (ED) are generally stable. Unfortunately, some will unexpectedly decompensate rapidly. This study explores these patients and their characteristics. Methods: This retrospective, observational study examined patients admitted to non-ICU settings at a community hospital. Patients were identified by rapid response team (RRT) activation, triggered by acute decompensation. ED chief complaint, reason for activation, and vital signs were compared between patients transferred to a higher level of care versus those who were not. Results: Throughout 2019, 424 episodes of acute decompensation were identified, 118 occurring within 24 h of admission. A higher rate of ICU transfers was seen in patients with initial ED chief complaints of general malaise (87.5% vs 12.5%, p  =  0.023) and dyspnea (70.6% vs 29.4%, p  =  0.050). Patients with sudden decompensation were more likely to need ICU transfer if the RRT reason was respiratory issues (47% vs 24%, p  =  0.010) or hypertension (9.1% vs 0%, p  =  0.019). Patients with syncope as a reason for decompensation were less likely to need transfer (0% vs 10.3%, p  =  0.014). Patients requiring ICU transfer were significantly older (74.4 vs 71.8 years, p  =  0.016). No differences in admission vital signs, APACHE score, or qSOFA score were found. Conclusions: Patients admitted to the floor with chief complaint of general malaise or dyspnea should be considered at higher risk of having a sudden decompensation requiring transfer to a higher level of care. Therefore, greater attention should be taken with disposition of these patients at the time of admission.